Levantamento de nematoides entomopatogênicos em áreas agrícolas e influência da temperatura e do substrato na sobrevivência, multiplicação e armazenamento - Brida, Andressa Lima de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Entomopathogenic nematodes (EPNs) show promising for biological control of pests. The abiotic factors, temperature, soil types and substrates, may influence the survival of infective juveniles storage and field conditions. The objectives of this study were to isolate and identify species of EPNs collected in areas of forestry, annual and fruit crops in Brazil; assess the period of mortality of larvae Galleria mellonella after infection of Heterorhabditis amazonensis IBCB 24, the emergency period and IJs (infective juveniles) multiplied during the 30-day period in five temperatures; evaluate the influence of temperature on survival IJs of Steinernema carpocapsae IBCB 02 Heterorhabditis amazonensis IBCB 24 and Steinernema feltiae IBCB 47 storage conditions; evaluate the influence of light and substrate on juvenile infection capacity of isolates IBCB 06 Steinernema brazilense, IBCB 02 Steinernema carpocapsae, IBCB 47 Steinernema feltiae and IBCB 24 Heterorhabditis amazonensis in larvae G. mellonella and evaluate the use of different substrates to prolong the survival of IJs of S. brazilense IBCB 06 and H. amazonensis IBCB 24 storage conditions. This study was divided into five chapters. After collecting data, the species were identified as H. amazonensis, S. rarum, M. rainai and O. tipulae. The at temperatures of 26°C and 30°C gave the shortest time period (three days) for the crawler mortality caused by H. amazonensis in G. mellonella. The shortest duration for emergency IJs was found at 30°C temperature (9.4 days). The average number of IJs produced at 26°C (229.563) was higher at all temperatures studied, but no statistical difference when compared to 30°C IJs produced in the temperature (127.157). The temperature of 22°C (223.886) did not differ statistically from the lower temperature ...

Nematoides entomopatogênicos (NEPs) são promissores para o controle biológico de pragas. Os fatores abióticos, temperatura e os tipos de solos e substratos, influenciam a sobrevivência de juvenis infectantes em condições de armazenamento e a campo. Os objetivos do presente estudo foram: isolar e identificar espécies de NEPs coletadas em áreas de culturas florestais, anuais e frutíferas no Brasil; avaliar o período de mortalidade de lagartas de Galleria mellonella após a infecção de Heterorhabditis amazonensis IBCB 24, o período da emergência e JIs (juvenis infectantes) multiplicados durante o período de 30 dias em cinco temperaturas; avaliar a influência da temperatura na sobrevivência JIs de Steinernema carpocapsae IBCB 02 Heterorhabditis amazonensis IBCB 24 e Steinernema feltiae IBCB 47 em condições de armazenamento; avaliar a influência da luminosidade e do substrato na capacidade de infecção de juvenis dos isolados IBCB 06 Steinernema brazilense, IBCB 02 Steinernema carpocapsae, IBCB 47 Steinernema feltiae e IBCB 24 Heterorhabditis amazonensis em lagartas de G. mellonella e avaliar o uso de diferentes substratos para prolongar a sobrevivência de JIs de S. brazilense IBCB 06 e H. amazonensis IBCB 24 em condições de armazenamento. O presente estudo foi dividido em cinco capítulos. Após a coleta de dados, as espécies foram identificadas como H. amazonensis, S. rarum, M. rainai e O. tipulae. As temperaturas de 26°C e 30°C proporcionaram o menor período de tempo (três dias) para a mortalidade de lagartas de G. mellonella causadas por H. amazonensis. O menor período de tempo para a 2 emergência de JIs foi na temperatura 30°C, (9,4 dias). O número médio de JIs produzidos a 26°C (229.563) foi superior a todas as temperaturas estudadas, mas sem diferença estatística quando comparado aos JIs produzidos na temperatura de 30°C (127.157). A temperatura de 22°C (223.88 ...
Survey of entomopathogenic nematodes in agricultural areas and it influences of temperature and substrates on survival, multiplication and storage
Keywords: Nematóides entomopatogênicos - Identificação; Pragas agricolas - Controle biologico; Substratos; Agricultural pests